Bahaya Hoaks dan Urgensi Literasi Media: Studi pada Mafindo Solo Raya - Riza Dwi Maqruf (UIN Raden Mas Said Surakarta, 2021)
This research was based on the massive political hoax circulating on social media. The spread of hoaxes was increasing day by day with the 2019 simultaneous election. Hoax became an important problem in society because the level of community literacy was still low. The Indonesian Anti Hoax Society (MAFINDO) Solo Raya invited the society to fight hoaxes in the 2019 political year. This study aims to describe how the media literacy strategies carried out by MAFINDO Solo Raya in overcoming hoaxes in the 2019 political year. The theory used in this research was Potter literacy media. This research used a descriptive qualitative approach. The data collection technique used in this study were interviews, observation and documentation. The results of this research indicated that MAFINDO Solo Raya's media literacy strategies in overcoming hoaxes in the 2019 political year used socialization, education and fact checking training with the Hoax Buster Tools application.